NILAI-NILAI SOSIAL DALAM AL-QUR’AN DAN HADIS: FONDASI PENDIDIKAN MASYARAKAT DI KECAMATAN HARUYAN - norhapijah; Basir, Abdul; Barni, Mahyudin (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2025)
This study aims to examine the social values in the Qur'an and Hadith and their relevance as the foundation for the education of the Islamic community in Haruyan District. The background of this research stems from the phenomenon of weakening the practice of Islamic social values in community life, which leads to the emergence of social disharmony. The research uses a qualitative approach with a literature study method combined with limited social observation to link Islamic normative teachings with the social realities of the local community. The findings show that social values in Islam encompass three main dimensions: love, responsibility, and life harmony. These values are strongly reflected in Surah Al-Hujurat verses 11–13, which emphasize respect for human dignity, the prohibition of prejudice and gossip, and the principle of ta’aruf (getting to know each other) as the foundation for harmonious social relations. The teachings of the Prophet Muhammad (peace be upon him) further strengthen these values through teachings on guarding the tongue, respecting neighbors and guests, and loving fellow Muslims. In the context of the Haruyan District community, these Islamic social values are highly relevant as the basis for community education because they help strengthen social cohesion, form ethical character, and encourage social participation and community empowerment. This study affirms that the internalization of social values based on the Qur'an and Hadith in community education significantly contributes to the realization of a harmonious, inclusive, and sustainable social life.